Science and Technology Policy in the United States : Open Systems in Action - Kraemer, Sylvia K. (Book collections on Project MUSE., 2006)
In this lucidly-written introduction to the topic, Sylvia Kraemer draws upon her extensive experience in government to develop a useful and powerful framework for thinking about the American approach to shaping and managing scientific innovation. Kraemer suggests that the history of science, technology, and politics is best understood as a negotiation of ongoing tensions between open and closed systems. Open systems depend on universal access to information that is complete, verifiable, and appropriately used. Closed systems, in contrast, are composed of exclusive and often proprietary feature.